Pakistan : Country Gender Assessment, Bridging the Gender Gap, Opportunities and Challenges - World Bank (Washington, DC, 2012)
If Pakistan is to reduce gender gaps and achieve its development goals, policy interventions will require a dual focus on near-term and long-term outcomes. In the near term, females need access to basic services and opportunities. In the longer term the economic, cultural, and political environment must sustain improved circumstances for women in health, labor force participation, and other outcomes. Far deeper and more integrated initiatives are needed if long-standing trends in gender inequality are to be reversed. What role does public policy play? In many cases minor changes in laws and institutions can foster greater involvement by women in the public sphere to enable them to pursue activities that further enhance their autonomy and elevate their status. Such changes may encourage parents to educate their daughters, for instance, which will enable future generations of women to make better health-related and economic decisions within the household, and to participate in political life where they can contribute to further social and legal change. What is to be done in the meantime, as institutional reforms and economic growth may make limited and slow progress? Active policy measures to promote gender equality in the present are crucial. In particular, near-term approaches must work around existing constraints on women and girls, augmenting their access to basic services, paid work, and opportunities for decision-making in the public sphere. The analysis in this report has incorporated research and insights from scholars and civil society organizations in Pakistan in order to arrive at precisely these types of near-term approaches.